2019
DOI: 10.1161/jaha.119.013296
|View full text |Cite
|
Sign up to set email alerts
|

ST‐Segment–Elevation Myocardial Infarction (STEMI) Patients Without Standard Modifiable Cardiovascular Risk Factors—How Common Are They, and What Are Their Outcomes?

Abstract: BackgroundPrograms targeting the standard modifiable cardiovascular risk factors (SMuRFs: hypertension, diabetes mellitus, hypercholesterolemia, smoking) are critical to tackling coronary heart disease at a community level. However, myocardial infarction in SMuRF‐less individuals is not uncommon. This study uses 2 sequential large, multicenter registries to examine the proportion and outcomes of SMuRF‐less ST‐segment–elevation myocardial infarction (STEMI) patients.Methods and ResultsWe identified 3081 STEMI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
113
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 30 publications
10
113
2
1
Order By: Relevance
“…In this study, all patients > 40 years old were found. This is in accordance with the research of previously report from GRACE and CONCORDANCE data in australia which found the median age of patients experiencing STEMI which is 61 years (52 years-69 years) (Vernon et al, 2019). This is consistent with a population study conducted by Jousilahti et al, (1999) who found that the incidence rate of coronary heart disease was three times greater in men than women and mortality rate was five times greater in men than women.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, all patients > 40 years old were found. This is in accordance with the research of previously report from GRACE and CONCORDANCE data in australia which found the median age of patients experiencing STEMI which is 61 years (52 years-69 years) (Vernon et al, 2019). This is consistent with a population study conducted by Jousilahti et al, (1999) who found that the incidence rate of coronary heart disease was three times greater in men than women and mortality rate was five times greater in men than women.…”
Section: Discussionsupporting
confidence: 93%
“…ST-segment-elevation myocardial infarction (STEMI) is considered the most common and severe acute myocardial infarction (AMI) [1]. According to current guidelines, early reperfusion of coronary flow by primary percutaneous coronary intervention (PPCI) significantly mitigates cardiac cell death and cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Several tools for cardiovascular disease risk and prognosis evaluation in different populations have been established to guide clinical practice. e widely used tools included the Framingham general CVD equations in the United States, the QRISK in the United Kingdom, the Systematic Coronary Risk Evaluation model in Europe, and the Pooled Cohort Equations for atherosclerotic CVD (ASCVD) released in the American Heart Association guideline, as well as rombolysis in Myocardial Infarction (TIMI) risk score, TIMI risk index, Evaluation of Methods and Management of Acute Coronary Events (EMMACE), Global Registry of Acute Coronary Events (GRACE), Primary Angioplasty in Myocardial Infarction (PAMI), and Canada Acute Coronary Syndrome (C-ACS) Risk Score [7][8][9][10][11][12][13][14][15][16]. However, these equations presented above were all derived from Western populations, which limited their application to other populations.…”
Section: Introductionmentioning
confidence: 99%